(untitled) (Research, Society and Development, 2022)
In the course of cardiac surgery with cardiopulmonary bypass (CPB) many factors come into play. A lot of care is needed, in addition to the surgery itself, especially with regard to blood oxygenation, blood pressure and the formation of microemboli, which will directly influence the pathogenesis of neurological abnormalities found in the postoperative period. Elevations in the values ​​of intracranial pressure (ICP) in adults can be small to severe, and may pose a threat to the patient’s life, according to this increase. The objective of the present study is to discuss possible changes in the ICP of patients who underwent cardiac surgery as possible consequences of CPB. Since perfusion triggers the Systemic Inflammatory Response Syndrome, directly and indirectly interfering with the mechanisms that maintain brain compliance, such changes in ICP may occur as a consequence of CPB, however, investigations are needed to explain this possible relationship.